Mimicking Antigen-Driven Asthma in Rodent Models—How Close Can We Get? - Alessandrini, Francesca; Musiol, Stephanie; Schneider, Evelyn; Blanco-Pérez, Frank; Albrecht, Melanie (Frontiers in Immunology, 2020)
Asthma is a heterogeneous disease with increasing prevalence worldwide characterized by chronic airway inflammation, increased mucus secretion and bronchial hyperresponsiveness. The phenotypic heterogeneity among asthmatic patients is accompanied by different endotypes, mainly Type 2 or non-Type 2. To investigate the pathomechanism of this complex disease many animal models have been developed, each trying to mimic specific aspects of the human disease. Rodents have classically been employed in animal models of asthma. The present review provides an overview of currently used Type 2 vs non-Type 2 rodent asthma models, both acute and chronic. It further assesses the methods used to simulate disease development and exacerbations as well as to quantify allergic airway inflammation, including lung physiologic, cellular and molecular immunologic responses. Furthermore, the employment of genetically modified animals, which provide an in-depth understanding of the role of a variety of molecules, signaling pathways and receptors implicated in the development of this disease as well as humanized models of allergic inflammation, which have been recently developed to overcome differences between the rodent and human immune systems, are discussed. Nevertheless, differences between mice and humans should be carefully considered and limits of extrapolation should be wisely taken into account when translating experimental results into clinical use.